`y=ln(e^-x+xe^-x)`

`y'=1/(e^-x+xe^-x) d/dx(e^-x+xe^-x)`

`y'=(1/(e^-x+xe^-x))(-e^-x+e^-x+x(-1)e^-x)`

`y'=(-xe^-x)/(e^-x+xe^-x)`

`y'=(-x)/(e^x(e^-x+xe^-x))`

`y'=(-x)/(e^0+xe^0)`

`y'=-x/(x+1)`

`y = ln{(e^-x) + x*(e^-x)}`

taking antilog both sides we get

`e^y = (e^-x) + x*(e^-x)`

differentiating both sides

`(e^y)dy/dx = -(e^-x) -x*(e^-x) + (e^-x)`

`dy/dx = (e^-y)*[-x*(e^-x)]`

`or, dy/dx = {-x(e^-x)}/{(e^-x) + x*(e^-x)}`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now